Correction: Nulsopapon et al. The Synergistic Activity and Optimizing Doses of Tigecycline in Combination with Aminoglycosides against Clinical Carbapenem-Resistant Klebsiella pneumoniae Isolates. Antibiotics 2021, 10, 736 - Parnrada Nulsopapon; Worapong Nasomsong; Manat Pongchaidecha; Dhitiwat Changpradub; Piraporn Juntanawiwat; Wichai Santimaleeworagun (MDPI AG, 2022)
There were errors made in the original article [...]